Balcony and Jalousi Effectiveness Review to Promote Daylight in Interior for Tropical Country - Tedjokoesoemo, Purnama Esa Dora (Institute of Research and Community Outreach - Petra Christian University, 2014)
City growth will eventually affect its people lifestyle. Higher buildings, which serve higher economic value, will need to be supported with open area for social interaction. The three principal of sustainable design is not only to embrace the economic growth, but also to consider social interaction and ecology in it. Since the colonial era Balconies and jalousies are well known as architectural elements that provide more space for interaction, economically possible to make use of, and provide shading for the space underneath. This research will investigate how these elements efficiency will affect the introduction of daylight into interior space to save energy. This quantitative research was conducted with IES-VE 2012 software with embedded suncast, Flucs-DL, and Radiance software in it to calculate the depth of daylight penetration and glare potential. The simulation was set in tropical country (Singapore).